Polarization of light with applications in optical fibers - Kumar, Arun, 1952-; Ghatak, A. K. (Ajoy K.), 1939-; Society of Photo-optical Instrumentation Engineers (Bellingham, Wash. : SPIE Press)
Includes bibliographical references and index